PEMILIHAN DAN PEMBENTUKAN PORTOFOLIO SAHAM LQ45 YANG OPTIMAL (STUDI KASUS DI BURSA EFEK INDONESIA (BEI) - Desy Wahyuningrum (Journal of Indonesian Applied Economics, 2010)
This article aims to identify how investor choose and decide an optimal portfolio ofstock, using Markowitz and Single  Index Model. The analysis on 45 Shares  in  thegroup of LQ45 in Indonesia Stock Exchange (IDX), found that the optimal portfoliowould be composed of 11 share: TRUB (Truba Alam Manunggal Engineering Tbk),BUMI  (Bumi Resources Tbk), TINS (Timah Tbk  ), BNBR (Bakrie & Brothers Tbk),BBNI (Bank Negara Indonesia Tbk), and ELTY (Bakrieland Development Tbk). As acomparison  of  risk  and  return  of  optimal  and  non-optimal  portfolio,  the  optimalportfolio had 14.6% return and 1.6% risk, while the non-optimal had only 7.8% re-turn  and 0.13% risk.Keywords: Markowitz Model, Single Index Model, LQ45, Indonesia Stock Exchange,optimal portfolio, risk, return